Assessing sexual dimorphism in the common vampire bat, Desmodus rotundus - Analorena Cifuentes-Rincon; Karen D. Sarmiento-Arias; Diego Soler-Tovar; Abelardo Rodríguez-Bolaños; Carlos Bravo-Garcia; Nicolas Reyes-Amaya; Laura Ávila-Vargas; Luis E. Escobar (PLoS ONE, 2026)
Sexual dimorphism in bats is understudied, with conflicting evidence across species and geographic regions. For Desmodus rotundus , the common vampire bat, previous reports on morphological sex differences have been inconsistent. This study aimed to assess sexual dimorphism in D. rotundus using a combination of contemporary field measurements and historical museum specimens. We analyzed six morphometric traits, including body mass, head length, body length, tibia length, ear length, and forearm length. Data were collected from 46 wild-captured individuals from five locations across Colombia in South America. Additionally, forearm length was examined in an expanded dataset of 490 specimens, including additional 444 individuals from museum vouchers collected over the past century. Principal components analysis and hierarchical clustering of the six-trait dataset showed patterns of differentiation between sexes, with partial overlap. Forearm length, analyzed independently in the full 490-specimen dataset, showed strong evidence of sexual dimorphism. Females had significantly longer forearms (mean = 61.8 mm) than males (mean = 58.5 mm), with non-overlapping 95% confidence intervals and a highly significant t-test result (t = −12.68, p < 2 × 10 ⁻ ¹⁶). Sex explained 25.7% of the variation in forearm length (R² = 0.26). Tibia length also differed significantly between sexes of the wild-catch individuals (p = 0.004), with females exhibiting greater values. Comparisons between museum specimens (historical) and wild-caught specimens (contemporary) showed no significant differences across time in either sex. Among females, the difference was not significant (t = −0.93, df = 208, p = 0.355), and the same was true for males (t = −0.01, df = 278, p = 0.992). A follow-up MANOVA on the six morphometric traits indicated a significant effect of sex (Pillai’s trace = 0.389, approx. F(6,39)=4.14, p < 2.2 × 10 ⁻ ¹⁶). After correcting for multiple comparisons, significant sexual dimorphism remained for forearm and tibia lengths, with forearm showing the strongest signal. These findings provide robust support for modest but consistent female-biased dimorphism in D. rotundus . The use of both multivariate and univariate analysis, combined with long-term historical data, enhanced the reliability of signals detected regarding morphological differences. Desmodus rotundus play a role as a primary reservoir for zoonotic viruses, has potential relevance in biomedical research, and provides ecosystem services. Understanding sex-based morphological variation is critical to inform public health, ecology, and biological conservation strategies. Females were consistently larger than males, but segregation was not absolute, with some individuals falling outside the expected data range for their sex. This study contributes to a clearer understanding of morphological variation and lays the groundwork for future research into the ecological and evolutionary drivers of dimorphism in bats.